Teaching Basic Qur’an and its Values to Local Children at Surau Wang Ulu Perlis, Malaysia - Huda, Rahmat; Sanusi, Afriadi; Abunawas; Khairul Amri; Akhmad Tarmizi; Muhammad Darwis (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service project aimed to strengthen Basic Qur’anic literacy and its Islamic values among children at Surau Wang Ulu, Perlis, Malaysia. The initiative combined structured Qur’an teaching sessions, value-based storytelling, and participatory activities involving students of Universiti Muhammadiyah Malaysia and local children. Using direct method or recitation practice to comprehend values beyond the surah. The findings highlight the surau’s role as a vital institution for early religious education and character formation, while also offering a replicable model for similar communities across children Islamic values acquisition.